Human DNA polymerase lambda diverged in evolution from DNA polymerase beta toward specific Mn(++) dependence: a kinetic and thermodynamic study. - Blanca, G; Shevelev, I; Ramadan, K; Villani, G; Spadari, S; Hübscher, U; Maga, G (2003)
The recently discovered human DNA polymerase lambda (DNA pol lambda) has been implicated in translesion DNA synthesis across abasic sites. One remarkable feature of this enzyme is its preference for Mn(2+) over Mg(2+) as the activating metal ion, but the molecular basis for this preference is not known. Here, we present a kinetic and thermodynamic analysis of the DNA polymerase reaction catalyzed by full length human DNA pol lambda, showing that Mn(2+) favors specifically the catalytic step of nucleotide incorporation. Besides acting as a poor coactivator for catalysis, Mg(2+) appeared to bind also to an allosteric site, resulting in the inhibition of the synthetic activity of DNA pol lambda and in an increased sensitivity to end product (pyrophosphate) inhibition. Comparison with the closely related enzyme human DNA pol beta, as well as with other DNA synthesising enzymes (mammalian DNA pol alpha and DNA pol delta, Escherichia coli DNA pol I, and HIV-1 reverse transcriptase) indicated that these features are unique to DNA pol lambda. A deletion mutant of DNA pol lambda, which contained the highly conserved catalytic core only representing the C-terminal half of the protein, showed biochemical properties comparable to the full length enzyme but clearly different from the close homologue DNA pol beta, highlighting the existence of important differences between DNA pol lambda and DNA pol beta, despite a high degree of sequence similarity.